Manajemen Pembelajaran Tahfidzul Quran Berbasis Metode Yaddain Di Mi Plus Darul Hufadz Sumedang - Ari Prayoga; Rizqia Salma Noorfaizah; Yaya Suryana; Mohammad Sulhan (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2019)
Management of tahfidz al-Quran learning in terms of organizing educators has a lack of human resources. The implementation of tahfidz learning in practice has not been effectively evenly implemented by educators. This study aims to uncover the processes of planning, organizing, implementing, evaluating, of the tahfidz al-Quran learning based on the Yaddain method in the Madrasah Ibtidaiyah Plus Darul Hufadz Sumedang. The research method used is qualitative. Data collection techniques used the technique of in-depth interviews, observation, and documentation study. The results of the study show: first, planning is carried out by making learning concepts that are detailed with short-term, mid-term, and long-term planning, formulated through syllabi and Learning Implementation Plans (RPP); second, organizing is carried out by determining the tasks and stages in the tahfidz Quran learning process; third, the implementation is carried out with class management, scheduling, activity mechanisms including opening, core and closing activities; fourth, evaluation is carried out by monitoring students with individual student absenteeism while taking part in learning, repeating mid-semester and final examinations.